FIGURATIVE LANGUAGE USED IN THE LYRICS OF AYU TING TING’S SONGS - Yutika Sari; Afrida Hanum (Universitas Islam Sumatera Utara (UISU), 2018)
In a song, we can find lyrics which complete and beautify the song and makes the hearer more interested in hearing it. There are many kinds of genres in song. Dangdut is one of them. Nowadays dangdut song is not as good as it used to be and contains uneducated lyrics. In some lyrics, there are many words written using figurative languages. This study focused on analyzing the kinds figurative language that occur in the lyrics of Ayu Ting-Ting’s songs. It consists of four songs. The researchers choose these songs because there are so many figurative languages found in the songs lyrics. Therefore, this reserach examined what types of figurative language and the most dominant are used in Ayu Ting Ting’s songs. The research used descriptive qualitative approach supported by quantitative data in order to explore behaviour, perspective, feeling, and experience as figurative meaning. This research carried out by formulating problem, collecting data, classifying data and analyzing data. After investigating the sentence in the songs lyrics, the researchers found five kinds of figurative language and four songs lyrics that have figurative language. From 4 songs lyrics, there are 9 items of hyperbole, 3 items of metaphor, 11 items of personification, 7 items in paradox, and 1 item of oxymoron. The dominant of figurative language used in the song lyrics is personification and the least is oxymoron.